After-discharge in the upper airway muscle genioglossus following brief hypoxia. Issue 9 (1st April 2021) - Avraam, Joanne; Dawson, Andrew; Feast, Nicole; Fan, Feiven Lee; Fridgant, Monika D; Kay, Amanda; Koay, Zi Yi; Jia, Pingdong; Greig, Rachel; Thornton, Therese; Nicholas, Christian L; O'Donoghue, Fergal J; et al.
Abstract: Study Objectives: Genioglossus (GG) after-discharge is thought to protect against pharyngeal collapse by minimizing periods of low upper airway muscle activity. How GG after-discharge occurs and which single motor units (SMUs) are responsible for the phenomenon are unknown. The aim of this study was to investigate genioglossal after-discharge. Methods: During wakefulness, after-discharge was elicited 8–12 times in healthy individuals with brief isocapnic hypoxia (45–60 s of 10% O2 in N2 ) terminated by a single breath of 100% O2 . GG SMUs were designated as firing solely, or at increased rate, during inspiration (Inspiratory phasic [IP] and inspiratory tonic [IT], respectively); solely, or at increased rate, during expiration (Expiratory phasic [EP] or expiratory tonic [ET], respectively) or firing constantly without respiratory modulation (Tonic). SMUs were quantified at baseline, the end of hypoxia, the hyperoxic breath, and the following eight normoxic breaths. Results: A total of 210 SMUs were identified in 17 participants. GG muscle activity was elevated above baseline for seven breaths after hyperoxia ( p < 0.001), indicating a strong after-discharge effect. After-discharge occurred due to persistent firing of IP and IT units that were recruited during hypoxia, with minimal changes in ET, EP, or Tonic SMUs. The firing frequency of units that were already active changed minimally during hypoxia or the afterdischarge period ( p > 0.05). Conclusion: That genioglossal after-discharge is almost entirely due to persistent firing of previously silent inspiratory SMUs provides insight into the mechanisms responsible for the phenomenon and supports the hypothesis that the inspiratory and expiratory/tonic motor units within the muscle have idiosyncratic functions.